2018
DOI: 10.1159/000486829
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Renoprotective Effects of Thymoquinone

Abstract: Background: Kidneys as vital organs remove waste material from blood. Additionally, they may also have a role in the electrolyte balance, regulation of blood pressure, and red blood cell genesis. Kidney diseases may be caused by several factors such as ischemia/reperfusion injury, diabetes, and nephrotoxic agents. Oxidative stress and inflammation are involved in the pathogenesis and progression of kidney diseases. Traditionally, natural antioxidants are used for treatment of renal failure in various countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Previous studies showed a key role of inflammation in the development and progression of DN (20,21). Furthermore, strategies targeting inflammatory molecules have been shown to be beneficial in treating DN (1820).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed a key role of inflammation in the development and progression of DN (20,21). Furthermore, strategies targeting inflammatory molecules have been shown to be beneficial in treating DN (1820).…”
Section: Discussionmentioning
confidence: 95%
“…Diabetic nephropathy is the main reason of morbidity and death in diabetic people. Effective therapeutic agents are needed to stop the progression of this disease and to improve kidney damage (Shaterzadeh-Yazdi et al, 2018).…”
Section: Pas Stainingmentioning
confidence: 99%
“…In addition, kidney tissue in the following stages; histopathological changes such as capsular, glomerular and tubular basement membrane thickening, mesangial matrix enlargement, loss of podocytes, degeneration in the tubular epithelium and macrophage infiltration are observed. ESRF, the last stage of the disease, is characterized by irreversible structural changes such as glomerulosclerosis and tubulointerstitial fibrosis (Kanwar et al, 2008;Kanter, 2009;Roshan & Stanton, 2013;Al-Trad et al, 2016;Shaterzadeh-Yazdi et al, 2018). In patients with type 1 and type 2 diabetes, using drugs with blocking effect on the renin-angiotensin-aldosterone system, controlling hypertension, as well as using drugs to control dyslipidemia and hyperglycemia are the most effective treatment strategies in reducing the progression of DN and cardiovascular mortality (Gross et al, 2005;Skupien et al, 2012;Levey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also filter water out from the filtrate and may thus concentrate and accumulate these toxic substances. 3,4 DMBA exposure has been shown to induce marked histological alternations in kidney, e.g., dilation of tubules and sloughing of the epithelium (signifying enhanced disintegration of tubules); with the epithelial cells of proximal convoluted tubules and Bowman's capsule being especially sensitive to DMBA-induced toxicity. 5,6…”
mentioning
confidence: 99%